2004
DOI: 10.21273/hortsci.39.7.1768
|View full text |Cite
|
Sign up to set email alerts
|

Velvet and Creeping Bentgrass Tolerance to Fenoxaprop

Abstract: The tolerance of velvet bentgrass (Agrostis canina L.) to the herbicide fenoxaprop is not known. In greenhouse experiments velvet bentgrass cultivars SR7200 and Vesper had a much greater degree of tolerance to fenoxaprop at rates ranging from 0.01 to 0.30 kg·ha-1 relative to L-93 creeping bentgrass (Agrostis stolonifera L.). SR7200 and Vesper were tolerant to fenoxaprop at 0.15 kg·ha-1 or lower and growth re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…Shim and Johnson (1992) noted sequential applications of fenoxaprop at 70 to 200 kg • ha -1 caused unacceptable injury to creeping bentgrass, and turf did not fully recover after 3 months compared with nontreated. Henry and Hart (2004) reported creeping bentgrass density was reduced up to 33% from the nontreated after sequential applications of fenoxaprop at 40 or 70 g • ha -1 , respectively.…”
Section: /Ha) ----------------------------------(%) -----------------mentioning
confidence: 91%
“…Shim and Johnson (1992) noted sequential applications of fenoxaprop at 70 to 200 kg • ha -1 caused unacceptable injury to creeping bentgrass, and turf did not fully recover after 3 months compared with nontreated. Henry and Hart (2004) reported creeping bentgrass density was reduced up to 33% from the nontreated after sequential applications of fenoxaprop at 40 or 70 g • ha -1 , respectively.…”
Section: /Ha) ----------------------------------(%) -----------------mentioning
confidence: 91%
“…This procedure was conducted again 3 wk after sequential treatments. Previous research evaluated 3‐wk clipping production to describe turfgrass response to herbicides (Henry and Hart, 2004; Cooper et al, 2016). This methodology was chosen to accumulate more clipping biomass for ease of determining cultivar response differences to metamifop rate.…”
Section: Methodsmentioning
confidence: 99%
“…ha −1 exhibited color ratings of 2.6 to 2.9. Henry and Hart (2004) observed a 20 and 40% reduction in clipping weight 4 wk after treatment of ‘L‐93’ creeping bentgrass with fenoxaprop at 0.07 and 0.15 kg a.i. ha −1 , respectively.…”
mentioning
confidence: 99%
“…Higgins et al (1987) reported that fenoxaprop at 0.06 and 0.13 lb/acre did not reduce creeping bentgrass color ratings below 4.5, while fluazifop at 0.09, 0.18, and 0.27 lb/acre reduced creeping bentgrass color ratings below 2.9 14 DAT. Henry and Hart (2004) observed a 20% and 40% reduction in clipping weight 4 weeks after treatment (WAT) of 'L-93' creeping bentgrass in response to fenoxaprop at 0.06 and 0.13 lb/acre. Reductions in turfgrass quality not only affect creeping bentgrass aesthetic appearance but may also reduce its competition, making it more susceptible to invasion from other weeds [e.g., annual bluegrass (Poa annua L.)] (Johnson, 1984;Turner et al, 1979).…”
Section: Unitsmentioning
confidence: 99%